The Inherent Shield: Learning-Based Stress Symptoms Among People Diagnosed with Specific Learning Disability and Its Relationship with Dispositional Mindfulness - Nimrod Polak; Ephraim S. Grossman (Societies)
Background: Past research suggests that individuals with learning disabilities experience higher levels of emotional difficulties. Objective: The aim of the current study was to investigate the relationships between specific learning disabilities (SLDs) and learning-based stress symptoms (LBSSs). Further, this study examines whether dispositional mindfulness (DM) can be used as a moderating factor for these symptoms resulting from the same stressful learning experience. Methods: The sample consisted of 133 participants (73 male) aged 23–44 years (M = 34.41; SD = 9.69). In this sample, 56 reported that they have been officially diagnosed with a SLD. Participants completed an online survey comprising a demographics questionnaire, self-report SLD questionnaire, school learning-based stress symptoms, and five-facet mindfulness questionnaire (FFMQ-24). Results: Results revealed that participants with an SLD had higher levels of LBSSs compared to the general population. Furthermore, findings revealed that DM significantly predicts LBSS levels. Conclusions: The present study provides further evidence on the impact of learning experiences on stress symptoms among individuals with SLDs, and this phenomenon we have termed as “learning-based stress symptoms”. Additionally, our findings introduce novel evidence that DM may influence the relationship between LBSSs and SLDs, suggesting that a high level of DM can serve as a protective factor against these learning-based stress symptoms.